The importance of environmental education in the early years of elementary school - Rossignol, Vera Maria; Bobato, Francine Cordeiro (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
This article is the result of a bibliographical review, regarding Environmental Education in the years of elementary school, with the objective of identifying how Environmental Education is worked at this stage of teaching. The contents covered in elementary school include transversal themes such as the environment, cultural plurality, citizenship education, and are covered across all other subjects. The teacher, as a mediator of the teaching and learning process, seeks, through his methodological practices, to awaken an awareness of the environment in his students, using appropriate tools to discuss the topic with students. In the various forms used in the development of Environmental Education, diversity depends on the participation of the community in the organization of projects, parents of students play an important role, with participation in the assembly of project structures related to practical studies used in elementary schools, becoming more cooperative, developing expectations about the recovery of the environment. Environmental Education in schools contributes to the formation of conscious citizens capable of deciding and acting in the socio-environmental reality, committed to society.